PENGEMBANGAN ALAT BANTU PENGEDITAN VIDEO DAN MULTIMEDIA BERBASIS ARDUINO USB MIDI - Setiyo Adi Nugroho; Andik Prakasa Hadi; Rudjiono Rudjiono (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2023)
The extensive use of multimedia technology in the film and television industry has greatly enhanced the aesthetics and artistry of film and television works, thereby fundamentally driving the development of the film and television industry. This development of needs in video and multimedia directly impacts the needs in the video editing process. Therefore, in the big video era, changes in the way video is used in various media including social media have had a big impact on editing video content. In speeding up the performance of video and multimedia editing, a shortcut method is needed, usually using a keyboard shortcut. keyboard shortcuts are obviously very helpful in the editing process but despite the fact that it usually takes half the time to issue commands to a computer application using those keyboard shortcuts, most people issue certain commands by clicking on icons on a toolbar or by selecting commands from a pull-down menu. In this study, a tool was designed by utilizing an Arduino microcontroller in the form of a midi controller which makes it easier to access shortcuts to help speed up the process of editing video and multimedia content.